Escalamiento de variedades de papa biofortificadas en Perú, con énfasis en la producción y distribución de semillas - Andrade-Piedra, J.L.; Perez, W.; Hareau, G.; Pradel, W.; Polar, Vivian; Ordinola, M.; Infantas, V.; Salas, E.; Burgos, G. (2025)
Iron-deficiency anemia remains a major public health challenge in Peru, particularly among young children and women in the Andean highlands. Biofortified potato varieties with elevated iron content offer a food-based, sustainable solution to improve dietary iron intake while strengthening smallholder livelihoods. This initiative presents an integrated strategy to scale biofortified potato varieties in Peru by combining breeding, seed systems strengthening, policy engagement, and market and nutrition linkages. Led by the International Potato Center (CIP) in collaboration with INIA and national partners, the approach focuses on accelerating the production and delivery of quality seed through in vitro plantlets, early generation seed systems, and partnerships with registered seed producers. The program aligns varietal deployment with public nutrition programs, local governments, NGOs, and private sector actors to promote consumption among priority populations, including children and women of reproductive age. Digital tools and monitoring platforms support tracking of varietal adoption and seed flows, enabling data-driven planning and continuous improvement. The initiative also emphasizes capacity development, institutional coordination, and policy alignment to ensure sustainability at scale. Together, these actions create an end-to-end pathway from breeding to nutrition impact, demonstrating how biofortified potatoes can contribute to improved health, resilient food systems, and inclusive rural development in Peru, with lessons applicable to other countries in Latin America and beyond.